1983
DOI: 10.1002/art.1780261003
|View full text |Cite
|
Sign up to set email alerts
|

Application of monoclonal antibodies to the characterization of cells eluted from human articular cartilage. Expression of Ia Antigens in Certain Diseases and Identification of an 85‐kD Cell Surface Molecule Accumulated in the Pericellular Matrix

Abstract: Ia antigens were strongly expressed on a considerable proportion of cells eluted from the damaged articular cartilages of certain individuals with osteoarthritis, rheumatoid arthritis, traumatic arthritis, or from osteochondromas. In contrast, Ia antigens were found on less than 1% of cells eluted from the more normal appearing cartilage of certain other patients with osteoarthritis, rheumatoid arthritis, osteonecrosis, femoral neck fractures, an enchondroma, and a chondrosarcoma. The cell preparations obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…However, studies with transgenic mice which express MHC genes in pancreatic islel cells have shown variable resuUs and no consistent evidence of autoimmunity to these tissues [47.48], Normalchondrocylesdo not express class II. but class II posi(ive eells have been reported in ()A and RA cartilage [16] and after IFN-y stimulalion [17], Our resuUs confirm this latter observation and show that IL-1^ may also induce these molecules but at a low intensity of expression. IL-1 production by RA synovium has been shown by others [49] lo correlate well with immunohistochemical staining for DR in synovial tisucs.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, studies with transgenic mice which express MHC genes in pancreatic islel cells have shown variable resuUs and no consistent evidence of autoimmunity to these tissues [47.48], Normalchondrocylesdo not express class II. but class II posi(ive eells have been reported in ()A and RA cartilage [16] and after IFN-y stimulalion [17], Our resuUs confirm this latter observation and show that IL-1^ may also induce these molecules but at a low intensity of expression. IL-1 production by RA synovium has been shown by others [49] lo correlate well with immunohistochemical staining for DR in synovial tisucs.…”
Section: Discussionsupporting
confidence: 79%
“…Aberrant DR expression may be induced by viral or other environmental agents and may be mediated by interferon-gamma (IFN-y) released following the activation of T lymphocytes. This aberrant DR expression, on chondrocytes for example, couid lead to the presentation of autoantigens to autologous T cells with subsequent tissue damage, HLA-DR molecules are not found on articular chondroeytes from normal articular eartilage but have been demonstrated in disease states [16] and after stimulation of normal ehondrocyles by IHN-y [I7[. Eflective T cell stimulation requires the presence of accessory cells and cytokines [l«.iy].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of MHC class II (formerly Ia) antigens has been demonstrated in human articular cartilage chondrocytes from patients with rheumatoid arthritis and osteoarthritis, while normal chondrocytes were class II-negative (Burmester et al, 1983;Lance et al, 1993). In tracheal cartilage, only a few chondrocytes express class II antigens (Shaari et al, 1998).…”
Section: Mhc Class II Antigens On Chondrocytesmentioning
confidence: 98%
“…Addressing these limitations, we focused on the development of 3-D culture models that would allow us to study the inflammatory joint process in the context of the extracellular matrix and to investigate the contribution of distinct cell populations such as chondrocytes (34,35) …”
mentioning
confidence: 99%